A Cross-Country Database of Fiscal Space - Kose, M. Ayhan; Kurlat, Sergio; Ohnsorge, Franziska; Sugawara, Naotaka (World Bank, Washington, DC, 2017)
This paper presents a comprehensive cross-country database of fiscal space, broadly defined as the availability of budgetary resources for a government to service its financial obligations. The database covers up to 200 countries over the period 1990-2016, and includes 28 indicators of fiscal space grouped into four categories: debt sustainability, balance sheet vulnerability, external and private sector debt related risks as potential causes of contingent liabilities, and market access. The authors illustrate potential applications of the database by analyzing developments in fiscal space across three time frames: over the past quarter century; during financial crises; and during oil price plunges. The main results are as follows. First, fiscal space had improved in many countries before the global financial crisis. In advanced economies, following severe deteriorations during the crisis, many indicators of fiscal space have virtually returned to levels in the mid-2000s. In contrast, fiscal space has shrunk in many emerging market and developing economies since the crisis. Second, financial crises tend to coincide with deterioration in multiple indicators of fiscal space, but they are often followed by reduced reliance on short-term borrowing. Finally, fiscal space narrows in energy-exporting emerging market and developing economies during oil price plunges but later expands, often because of procyclical fiscal tightening and, in some episodes, a recovery in oil prices.